Three new species of Philodendron (Araceae) from the Ducke Forest Reserve, central Amazonas, Brazil - Soares, M. Lourdes; Mayo, Simon Joseph (Feddes Repertorium, 2001)
Three new species of Philodendron from the Reserva Florestal Ducke near Manaus, Brazil are described and illustrated: Philodendron toshibai, Ph. hopkinsianum and Ph. tortum.
Keywords: Philodendron; Philodendron Hopkinsianum; Philodendron Tortum; Philodendron Toshibai